Analisis Faktor-Faktor Yang Mempengaruhi Kecelakaan Kerja Di Kapal Perspektif K3 - Fauzi Rahman Maulana; Rakha Kurnia Pradana; Muhammad Ichwan Setiawan; Muhammad Rakeen Firmansyah; Denny Oktavina Radianto (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
This research explores the factors contributing to the high rate of workplace accidents in the shipping industry, highlighting the complexity of challenges in enhancing safety. Key factors such as unexpected weather conditions, human error, lack of training, unsafe working environments, and high workload pressure create an environment susceptible to accidents. Holistic prevention efforts, including improved training and the implementation of advanced technology, are necessary to reduce risks. The study also emphasizes the unique work environment impacts, such as weather and the complexity of ship operations, as well as the psychological, organizational, and social influences on safety and occupational health. With a better understanding of these factors, it is hoped that more effective prevention strategies can be designed to create a safer working environment for ship crews.